(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article examines current radiation protection measures, established dose limits, and evidence-based strategies for minimizing occupational radiation exposure in healthcare settings. Contemporary research demonstrates that implementation of structured radiation safety programs, adherence to as low as reasonably achievable principles, and regular monitoring significantly reduce occupational doses among healthcare personnel. The analysis of recent data from 2020-2024 reveals that while average occupational doses remain well below regulatory limits, specific high-risk procedures and departments require enhanced protective measures. This comprehensive review synthesizes current international guidelines, technological advances in radiation protection, and emerging best practices to provide healthcare institutions with evidence-based recommendations for optimizing radiation safety programs.